2000
DOI: 10.1097/00007890-200006270-00012
|View full text |Cite
|
Sign up to set email alerts
|

Co-Transplantation of Donor-Derived Hepatocytes Induces Long-Term Tolerance to Cardiac Allografts in a Rat Model1

Abstract: We propose that donor hepatocytes induce permanent engraftment of syngeneic allografts by establishing a Th2 type alloresponse that is transferable to new graft recipients. The results of this study demonstrate that liver parenchymal cells significantly mediate spontaneously liver-induced tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…In similar rodent models, liver co-transplantation has been shown to prevent the rejection of skin allografts (159,173) and to reverse acute rejection of cardiac allografts (174). The protective effect of liver allografts may not require transplantation of the whole organ, as demonstrated by a rat study in which infusion of donor hepatocytes, but not hepatic leukocytes, into the portal vein prevented the rejection of cardiac allografts (175). In the clinical setting, liver co-transplantation has been shown to have a protective effect on small bowel (176), heart (177), and combined heart and lung (178) transplantation.…”
Section: The Liver Effectmentioning
confidence: 99%
“…In similar rodent models, liver co-transplantation has been shown to prevent the rejection of skin allografts (159,173) and to reverse acute rejection of cardiac allografts (174). The protective effect of liver allografts may not require transplantation of the whole organ, as demonstrated by a rat study in which infusion of donor hepatocytes, but not hepatic leukocytes, into the portal vein prevented the rejection of cardiac allografts (175). In the clinical setting, liver co-transplantation has been shown to have a protective effect on small bowel (176), heart (177), and combined heart and lung (178) transplantation.…”
Section: The Liver Effectmentioning
confidence: 99%
“…They surmised that mechanisms in the liver graft itself were involved in tolerance induction. Yoo‐Ott et al12 reported that donor‐derived hepatocytes protected cardiac allografts from acute and chronic rejection in rat. A chimeric liver probably has the ability to stimulate T cells via the indirect pathway 10.…”
Section: Discussionmentioning
confidence: 99%
“…In tissue and organ transplantation, the importance of the direct pathway in graft rejection has been stressed,6–8 and the indirect pathway has been suggested to be more important in graft rejection 9, 10. In liver transplantation, however, hepatocytes exert an immunologic effect on graft acceptance11 and appear to regulate both the direct and indirect pathways 12. Recent investigations have shown the role of the passenger leukocyte genotype in the rejection and acceptance of rat liver allografts 13.…”
mentioning
confidence: 99%
“…Çà â³äñóòíîñò³ îñòð³âö³â ï³äøëóíêîâî¿ çàëîçè àãðåãàòè ãåïàòîöèò³â äåãåíåðóâàëè, íå-çâàaeàþ÷è íà çàñòîñóâàííÿ öèêëîñïîðèíó À, çà-ëèøàþ÷è ëèøå òîíêèé øàð êë³òèí, ùî áåçïîñå-ðåäíüî ïðèëÿãàëè äî íèðêîâî¿ ïàðåíõ³ìè. Öå Êë³í³÷íà åíäîêðèíîëîã³ÿ òà åíäîêðèííà õ³ðóðã³ÿ 1(42) 2013 ÎÃËßÄÈ ñâ³ä÷èòü ïðî ìîaeëèâó ðîëü òðîô³÷íèõ ÷èííèê³â, ÿê³ ëîêàëüíî âèâ³ëüíÿþòüñÿ ç îñòð³âö³â ï³äøëóí-êîâî¿ çàëîçè [104]. Êîìá³íîâàíà àëîòðàíñïëàí-òàö³ÿ ãåïàòîöèò³â òà îñòð³âö³â ï³äøëóíêîâî¿ çà-ëîçè ó ñåëåç³íêó òàêîae ñïðèÿëà òðèâàë³øîìó âèaeèâàííþ êë³òèí (ïîíàä 1 ì³ñÿöü) ïîð³âíÿíî ç ïîîäèíîêèìè òðàíñïëàíòàòàìè ãåïàòîöèò³â [105].…”
Section: êë³í³÷íà åíäîêðèíîëîã³ÿ òà åíäîêðèííà õ³ðóðã³ÿ 1(42) 2013unclassified